A "Careful" Reading of Latin/x American Women's Electronic Literature. Issue 1 (1st March 2023) - Pitman, Thea
This article focuses on the recurrent narration of caring relationships and attempts to construct communities of care in electronic literature created by Latin/x American self-identified women. It addresses this topic by reading a select number of these works in relation to the significant body of theory that has emerged since the 1980s around feminist care ethics and its more recent updating to address questions of intersectionality, networked digital media, and our imbrication in networks of relationships with non-human entities. In particular, the article focuses on the narration and/or creation of non-heteronormative, non-white communities of care in works that have tended to be excluded from studies of Latin/x American electronic literature. Case studies thus include a number of queer cyberfeminist fiction and non-fiction blogs by the Afro-Cuban writers/academics/activists Yasmín S. Portales Machado and Sandra Abd'Allah-Álvarez Ramírez, as well as two science-fiction games/interactive narratives with trans of color protagonists made by Latina digital media and performance artist micha cárdenas and collaborators. It argues that the need to imagine and create alternative webs of care is of paramount importance for LGBTQI+ as well as racially marginalized groups, and that (networked) digital technologies have proven to be highly significant in terms of the way they can support the development of affinity-based groupings, as well as offering new ways of narrating complex and shifting intersectional identities and relationships.